Pengaruh Kemampuan, Motivasi dan Lingkungan Kerja terhadap Kinerja Pegawai Unit Pelaksana Teknis (UPT) PSDA di Pinrang, Sulawesi Selatan - Nurul Pratiwi; Baso Amang; Zaenal Arifin Sahabuddin (Jurnal Simki Economic, 2023)
This study aims to investigate the important factors determining employee performance in Kab. Pinrang, South Sulawesi. Three independent contructs were identified from prior research studies, namely ability, motivation, and work environment. A quantitative approach was adapted to examine the causality effects between variables. A total of 54 participants were determined as a sample, where they were permanent employees of the PSDA Task Implementation Unit (UPT) office, in Kab. Pinang, South Sulawesi, Indonesia. Data collection was performed for 2 months by disseminating a paper questionnaire. The data obtained were then tested using multiple regression. The results proved that ability, motivation, and work environment had a positive and significant impact on employee performance at Pinrang, Sul-Sel. These findings are practically beneficial as an insight and knowledge for HRM stratgies and further research guidance as well.